2015
DOI: 10.2166/hydro.2015.096
|View full text |Cite
|
Sign up to set email alerts
|

Meshless particle modelling of free surface flow over spillways

Abstract: A meshless Lagrangian (particle) method based on the weakly compressible moving particle semiimplicit formulation (WC-MPS) is developed and analysed for simulation of flow over spillways. To improve the accuracy of the model for pressure and velocity calculation, some modifications are proposed and evaluated for the inflow and wall boundary conditions implementation methods. The final model is applied for simulation of flow over the 45 W and 60 W ogee spillways (with different inflow rates) and also shallow fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The governing flow equations are given by (Jafari-Nodoushan) including mass conservation and motion in the Lagrangian frame for a weakly compressible flow, [26]:…”
Section: Governing Equations and Computational Schemementioning
confidence: 99%
“…The governing flow equations are given by (Jafari-Nodoushan) including mass conservation and motion in the Lagrangian frame for a weakly compressible flow, [26]:…”
Section: Governing Equations and Computational Schemementioning
confidence: 99%
“…Most data available in the literature has focused on heads near the design head and has shown that generally, discharge coefficients increased with increasing head ratio (Corps of Engineering, 1977;Erpicum et al, 2018;Jafari-Nodoushan et al, 2016;Kim & Park, 2005).…”
Section: Discharge Coefficientmentioning
confidence: 99%
“…Kanyabujinja (2015) used a two-phase CFD package Ansys-Fluent with realizable k-eddy viscosity closure and modeled flow domain of a typical ogee spillway, in two and three dimensions. A 2DV meshless Lagrangian model based on weakly compressible Moving particle Semi-implicit (MPS) method was developed by Jafari-Nodoushan, Hosseini, Shakibaeinia, and Mousavi (2016) to simulate pressure and velocity over ogee crest spillways. In a recent study, Fleit, Baranya, and Bihs (2018) introduced a numerical model, REEF3D, to predict water level and flow domain on an ogee type weir for both conditions of free surface and submerged flow.…”
Section: Introductionmentioning
confidence: 99%
“…The WC-MPS method, compared to the standard MPS method, requires less computer memory and potentially can speed-up the simulations. The WC-MPS method is validated through the simulation of several free-surface problems including flow over spillways [30] and flow over the sills and in trenches [28].…”
Section: Introductionmentioning
confidence: 99%